2022
DOI: 10.3390/ma15072646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tooth Movement Accuracy with Aligners: A Prospective Study

Abstract: Background. Clear aligners treatment (CAT) is a common solution in orthodontics to treat both simple and complex malocclusions. This study aimed to evaluate the predictability of CAT, comparing the virtually planned and the achieved tooth movement at the end of stage 15, which is often the time of first refinement. Methods. Seventeen patients (mean age: 28.3 years) were enrolled in the study. Torque, tip and rotation were analyzed in 238 maxillary teeth on digital models at Pre-treatment (T0), at the end of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Plenty of investigations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] stated a high percentage of mesial-rotation of upper first molars in Class II malocclusion. In 2019, de Oliveira-Viganò et al stated that dental Class II show the highest levels of mesio-palatal rotation of the upper first molars [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plenty of investigations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] stated a high percentage of mesial-rotation of upper first molars in Class II malocclusion. In 2019, de Oliveira-Viganò et al stated that dental Class II show the highest levels of mesio-palatal rotation of the upper first molars [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed an accuracy of 99% for the expansion movement. Several studies [ 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] focused on the expansion movement with Clear Aligners, analysing the molar transversal movement predictability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodily retraction of relative upright incisors was also frequently encountered among extraction cases; this is a complicated tooth movement that requires adequate intrusion and torque control of the incisors [ 30 ]. Simon et al reported that root torque and the intrusion of incisors could not be fully achieved by clear aligners (42%) [ 31 ]; the Vincenzo’ sample torque for the central incisors and canines accounted for just 35% of movements [ 32 ]. These results showed that additional torque control of the incisors should be designed to increase the predictability of tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, clear aligners have become very popular for orthodontic treatment in adult patients, considering that they are more aesthetic, more comfortable and easier to manage in terms of both emergencies and oral hygiene as compared to braces [ 13 , 14 ]. Today, clear aligners are used to treat different malocclusions [ 15 , 16 ], thanks also to the improvement of auxiliaries and attachments and aligners materials [ 17 , 18 ], which allow the achievement of complex movements, such as rotation or torque [ 19 , 20 ]. However, there is a lack of literature describing the management of extractive cases using clear aligners, particularly with a single extraction in the lower arch.…”
Section: Introductionmentioning
confidence: 99%